Functionality and Food Applications of Plant Proteins - Li, Yonghui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The demand for plant proteins continues to increase due to the growing global population, rising protein deficiency, and their versatile environmental, functional, nutritional, and health benefits. Plant proteins represent a more sustainable source to (partially) supplement costly animal-based foods. Many factors can influence protein functionality and application, such as protein sources, production methods, molecular structures, chemical properties, food formulations and environment, and food processing techniques. The potential applications of plant proteins are diverse. This reprint covers diverse topics related to the characterization, chemistry, interaction, processing, modification, functionality, and/or application of various plant proteins in relation to human food.